The Boundedness of Generalized Fractional Integral Operators on Small Morrey Spaces - Syaifudin, Rizky Aziz; Karim, Corina; Marjono, Marjono; Rahman, Hairur (Mathematics Department, Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2024)
The small Morrey space is the set of locally Lebesgue integrable functions with norm defined supremum over radius of ball . This paper aims to prove the boundedness properties of the generality of fractional integral operators in small Morrey spaces using Hedberg-type inequality. The first, in this paper will be discuss to prove Hedberg-type inequality on small Morrey spaces using dyadic decomposition, H lder inequality, and doubling condition. Furthermore, by using the inequality, it can be proven that the boundedness of generalized fractional integral operators on small Morrey spaces.